2016
DOI: 10.1158/1078-0432.ccr-15-1912
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Suppressive Myeloid Cells Potentiates Checkpoint Inhibitors to Control Spontaneous Neuroblastoma

Abstract: Purpose: Neuroblastoma is the most common extracranial solid cancer type in childhood, and high-risk patients have poor prognosis despite aggressive multimodal treatment. Neuroblastoma-driven inflammation contributes to the induction of suppressive myeloid cells that hamper efficient antitumor immune responses. Therefore, we sought to enhance antitumor immunity by removing immunosuppression mediated by myeloid cells.Experimental

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(115 citation statements)
references
References 54 publications
4
111
0
Order By: Relevance
“…We found that only the combination of the two therapies was effective in achieving efficient immune-cell activation resulting in strong antitumor efficacy in the transgenic neuroblastoma mouse model 20 . Similar to the observations made by Pyonteck et al., 31 BLZ945 single treatment did not abolish myeloid cells in the tumor, probably due to the presence of cytokines sustaining myeloid cell survival in the tumor microenvironment 20 . Our further analysis revealed that in addition to the removal of suppressive myeloid cells, repolarization of myeloid cells by enhancing CXCL9, 10, and 11 production presented an essential regulator.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We found that only the combination of the two therapies was effective in achieving efficient immune-cell activation resulting in strong antitumor efficacy in the transgenic neuroblastoma mouse model 20 . Similar to the observations made by Pyonteck et al., 31 BLZ945 single treatment did not abolish myeloid cells in the tumor, probably due to the presence of cytokines sustaining myeloid cell survival in the tumor microenvironment 20 . Our further analysis revealed that in addition to the removal of suppressive myeloid cells, repolarization of myeloid cells by enhancing CXCL9, 10, and 11 production presented an essential regulator.…”
Section: Discussionsupporting
confidence: 89%
“…In neuroblastoma, infiltration of TAMs was correlated to metastatic disease and worse prognosis 15 . Targeting suppressive myeloid cells through CSF-1R inhibition provides a promising approach for solid cancers, 20,31,32 particularly when combined with checkpoint inhibitors 20,33 . Several clinical programs are currently evaluating the safety and therapeutic values of this combinatorial approach (NCT02452424, NCT02526017, NCT02323191, and starting in October 2016 NCT02829723).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is associated with poor survival in various human cancer and CSF-1R (CSF-1 receptor) targeting strategies have been explored [23]. In NB, it has been shown that CSF-1R+ myeloid cells predict poor survival in patients and, as a consequence, combining CSF-1R inhibitor (BLZ945) with PD-1/PD-L1 blocking agents induce robust antitumor effects against established aggressive tumors in the TH-MYCN murine neuroblastoma model [24]. …”
Section: Cd171 (L1-cam) Is Another Abundant Cell Surface Molecule Expmentioning
confidence: 99%